2008
DOI: 10.1002/crat.200711093
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurement of growth kinetics of {100} KDP crystal faces in the presence of polyphosphate impurities

Abstract: The face growth rate and critical supersaturation of {100} face were in situ measured using the laserpolarization-interference technique in the presence of potassium pyrophosphate, trimetric sodium phosphate and sodium hexametaphosphate impurities. The polyphosphate impurities inhibit the growth rate of prismatic faces. The face growth rate as a function of supersaturation at different impurity concentrations, as well as critical supersaturation as a function of impurity concentrations, was found in good agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…The growth rate of the (100) face was measured by the laser polarization interference system [15]. The schematic of the system was shown in Figure 1.…”
Section: Measurement Of Growth Ratementioning
confidence: 99%
See 1 more Smart Citation
“…The growth rate of the (100) face was measured by the laser polarization interference system [15]. The schematic of the system was shown in Figure 1.…”
Section: Measurement Of Growth Ratementioning
confidence: 99%
“…At high supersaturation, the shape became "chunky" finally. The growth rate R was calculated in terms of relationship between the laser intensity I and the crystal thickness [15] as…”
Section: Crystals and Aspect Ratiomentioning
confidence: 99%
“…High speed imaging processes has also been used to capture high resolution images on-line and perform real-time, in situ particle analysis [10,13,14,54]. Other methods reported for growth rate determination include atomic force microscopy (AFM) [55][56][57][58][59], Michelson interferometry [60][61][62][63][64] and laser polarization-interference techniques [65].…”
Section: Crystal Growth Rate Measurement Techniquesmentioning
confidence: 99%
“…The growth rate and dead zone of the (100) face of KDP crystal were measured by laser-polarizationinterference technique [4]. The supersaturation of the growth solution was controlled via the circular water.…”
Section: -mentioning
confidence: 99%
“…The effect of impurities in the solution on growth habit of KDP crystal has been extensively studied [1][2][3][4]. It has been confirmed that trivalent and divalent metallic cations are liable to be absorbed on (100) face and inhibit the movement of the growth step, resulting in (100) faces tapering [1].…”
Section: Introductionmentioning
confidence: 99%